Enzyme supplementation (phytase and xylanase) improves low quality diets in Nile tilapia - Roel M. Maas; Fotini Kokou; Marc C.J. Verdegem; Johan W. Schrama (Aquaculture Reports)
Due to the growing demand for aquafeed ingredients that do not compete with human feed, plant co and by-products, and thus antinutritional factors like non-starch polysaccharides and phytate are expected to increase. Endogenous enzymes that target anti-nutritional factors may aid this transition. This study examined whether low-quality ingredients, affect endogenous enzymes' effects on Nile tilapia (Oreochromis niloticus) growth, nutrient utilization, microbiota, and digesta characteristics (e.g., VFA production). Four experimental diets were tested in a 2 × 2 factorial design. The first factor was the level of low-quality ingredients (control versus high), affecting dietary levels of NSP and phytate. The second factor was enzyme supplementation (xylanase and phytase versus no supplementation). After the 42-day feeding trial, the remaining fish were belt-fed for 4–6 days to collect digesta along the gastrointestinal track. Growth successfully increased with enzyme supplementation. Enzymes impacted growth more for the low-quality diet (interaction effect). The growth for the control-quality diet without enzymes was comparable to the growth for the low-quality diet with enzymes, indicating that the enzymes countered the negative impact of the low-quality diet (about 190 g NSP/kg diet higher compared to the control diet). The enzymes increased phosphorus availability by 31 % for the control-quality diet and by 56 % for the low-quality diet. The enzymes also improved the NSP digestibility, which was primarily due to improved NSP constituent xylose and arabinose digestibility. Although digestibility improved, N efficiency and phosphorus availability seem to explain growth improvement. Distal VFA levels and the acetate-producing core taxon Cetobacterium somerae increased with enzyme supplementation, mostly in the control diet. Enzyme supplementation was successful in improving growth, digestibility, and nutrient utilization, with the effect often being stronger for the lower-quality diet. Thus, the lower-quality diet's larger enzyme supplementation improvement may help transition to ingredients that compete less with human food.